Ontogenetic dependence of Nile crocodile (Crocodylus niloticus) isotope diet‐to‐tissue discrimination factors. (22nd July 2021) - Woodborne, Stephan; Botha, Hannes; Huchzermeyer, David; Myburgh, Jan; Hall, Grant; Myburgh, Albert
Abstract : Rationale: The diet of wild Nile crocodiles ( Crocodylus niloticus ) is difficult to assess because they are cryptic and nocturnal predators that are extremely sensitive to disturbance by observers, and stomach content analysis is challenging, especially in large specimens. Stable light isotope analysis provides a means of assessing their diet, but diet‐to‐tissue discrimination factors have yet to be established for the species. Methods: Isotope ratio ( 15 N/ 14 N and 13 C/ 12 C expressed as δ 15 N and δ 13 C) analyses of scutes, claws, and blood of farmed crocodiles of different sizes were compared with the isotope values of their lifelong diet, which comprises chickens from a single supplier. Results: Systematic size dependence in the diet‐to‐tissue discrimination factors for scute collagen, scute keratin, and claw keratin is described in regression relationships against the snout to vent length. Fixed values are presented for erythrocytes and blood plasma because blood was not sampled from juveniles. Conclusions: The diet‐to‐tissue discrimination factors help assess the diet of wild crocodiles. The diet of crocodiles from Lake Flag Boshielo shows a clear ontogenic shift, as has been seen in other studies, and the results strongly indicate a dependence on the terrestrial food web rather than a fish diet. That this population may exploit a terrestrial diet highlights potential conflicts for conserving Nile crocodiles outside protected areas.